Driven but Drained: Implication of JD-R Theory on Emotional Exhaustion and Job Engagement and Exploring Their Impact on Job Satisfaction in Clinical Research Associates - Dixit, Garima (Digital Repository of Theses - SSBM Geneva, 2025)
Clinical Research Associates (CRAs) serve as the frontline warriors of clinical research—ensuring the integrity, quality, and safety of trials before life-saving medicines reach the market and ultimately, our homes. Their emotional well-being and job satisfaction are therefore not just individual concerns but critical pillars of effective clinical trial operations. This study explores the impact of job demands and job resources on emotional exhaustion, job engagement, and job satisfaction among CRAs in India. Anchored in the Job Demands–Resources (JD-R) model, a convergent mixed-methods approach was adopted, combining quantitative data from 403 CRAs with qualitative insights drawn from 15 semi-structured, exploratory interviews. The quantitative analysis, conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM), revealed that job demands—specifically workload, role ambiguity, and role conflict—were significant positive predictors of emotional exhaustion. In contrast, job resources such as job autonomy and the nature of work significantly enhanced job engagement. Notably, contingent rewards demonstrated a surprising negative relationship with engagement. Emotional exhaustion had a strong negative impact on job satisfaction, while job engagement emerged as a robust positive predictor. Interestingly, emotional exhaustion did not significantly affect job engagement—contradicting previous literature—and supervisor support had no significant direct effect on engagement, although significant impacts job satisfaction. Qualitative findings enriched the statistical outcomes, offering deeper insight into CRA experiences. Participants described emotional fatigue arising from overlapping responsibilities, unrealistic expectations, and blurred role boundaries. However, many maintained engagement through meaningful work, autonomy, and a strong sense of professional identity. Feelings of favoritism and a lack of transparency in reward systems eroded motivation, while supportive supervisors who demonstrated empathy and empowerment—rather than rigid control—were seen as instrumental to well-being. The study affirms the core tenets of the JD-R model while surfacing important contextual nuances—particularly the buffering role of intrinsic motivation and the critical importance of perceived fairness. It calls for clinical research organizations to cultivate work environments grounded in role clarity, autonomy, equitable recognition, and psychological safety. The study concludes with practical recommendations for managerial strategy and future research, offering both conceptual contributions and actionable insights into fostering CRA well-being in high-pressure, mission-critical settings. Keywords: Job Demands, Job Resources, Emotional Exhaustion, Job Engagement, Job Satisfaction, Workload, Role Conflict, Role Ambiguity, Supervisor Support, Nature of Work, Job Autonomy, Contingent Rewards, Clinical Research, Burnout, Clinical Research Associates, JD-R Model, Mixed Methods